Effects of human disturbance on broods of Red-breasted Mergansers Mergus serrator - Kahlert, Johnny (Wildfowl, 2025)
The effects of human disturbance on broods of Red-breasted Mergansers were studied at three Danish localities. Fast-moving boats (fishermen, windsurfers, and motor boats) were considered to have the greatest impact on Merganser broods a frequency of encounters and rate of disturbance were highest. The presence of fast-moving boats also caused the most significant modifications to time budgets. However, Merganser broods are considered quite resilient to human disturbance as they quickly resumed their former activities after disturbance, and at moderate disturbance levels, interruptions to comfort behaviour were compensated fro within 1 hours. However, on one locality with high disturbance levels and frequent high-speed boating, the survival of ducklings was reduced.